2007
DOI: 10.1086/510549
|View full text |Cite
|
Sign up to set email alerts
|

The Mid‐Infrared Spectrum of Star‐forming Galaxies: Global Properties of Polycyclic Aromatic Hydrocarbon Emission

Abstract: We present a sample of low-resolution 5-38 µm Spitzer IRS spectra of the inner few square kiloparsecs of 59 nearby galaxies spanning a large range of star formation properties. A robust method for decomposing mid-infrared galaxy spectra is described, and used to explore the behavior of PAH emission and the prevalence of silicate dust extinction. Evidence for silicate extinction is found in ∼1/8 of the sample, at strengths which indicate most normal galaxies undergo A V 3 magnitudes averaged over their centers.… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

99
1,476
8
7

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 878 publications
(1,590 citation statements)
references
References 90 publications
(102 reference statements)
99
1,476
8
7
Order By: Relevance
“…Smith et al 2007;Draine & Li 2007;Vogler et al 2005;Lu et al 2003;Genzel & Cesarksky 2000, and references therein) and, as indicated in Sect. 1, the λ 6.75 µm ISO band is no exception.…”
Section: The λ 675 µM Emissionmentioning
confidence: 82%
See 2 more Smart Citations
“…Smith et al 2007;Draine & Li 2007;Vogler et al 2005;Lu et al 2003;Genzel & Cesarksky 2000, and references therein) and, as indicated in Sect. 1, the λ 6.75 µm ISO band is no exception.…”
Section: The λ 675 µM Emissionmentioning
confidence: 82%
“…7 of Irwin & Madden 2006) and can be modeled as a blend of three spectral features at λ 7.42 µm, λ 7.60 µm, and λ 7.85 µm (Smith et al 2007). The λ 7.7 µm PAH complex, alone, can contribute nearly one-half of the total PAH luminosity and up to 10% of the total infrared luminosity (Smith et al 2007). Indeed, photometry of the λ 6.75 µm ISO band is normally taken as a direct proxy for the presence of PAH emission.…”
Section: The λ 675 µM Emissionmentioning
confidence: 99%
See 1 more Smart Citation
“…(9) 60 (38) 157 (101) 310 (193) 185 (104) 310 (110) 12.50−13.00 37 (28) 276 (231) 710 (576) 1240 (934) 1639 (1054) 596 (195) 146 (5) 12. 25−12.50 130 (114) 701 (631) 1264 (1068) 1270 (852) 694 (45) 84 (0) (6217) 4365 (3178) 3248 (1921) 2732 (1293) 864 (299) 456 (116) used PAHFIT (Smith et al 2007), assuming a powerlaw continuum and an extinction curve with a screen configuration (Kemper et al 2004). Free parameters are the normalizations of the PAH features, the normalization and the index of the power-law continuum, and the extinction.…”
Section: Characterization Of Pahsmentioning
confidence: 99%
“…Least squares fit of the PAH spectra in the Ames' database to the ISO SWS spectrum of the H ii Region IRAS 23133. From Cami et al (2008) routinely called the "PAH bands" and are used as probes of the ISM in extra-galactic environments (Smith et al 2007). PAHs are also thought to contribute to the interstellar extinction and to be among the carriers of the diffuse interstellar absorption bands (DIBs).…”
Section: Overviewmentioning
confidence: 99%